The Evolution of an Innovative Online Task to Monitor Children's Oral Narrative Development - Scott, Amy; Gillon, Gail; McNeill, Brigid; Kopach, Alex (Frontiers in Psychology, 2022)
Oral narrative abilities are an important measure of children’s language competency and have predictive value for children’s later academic performance. Research and development underway in New Zealand is advancing an innovative online oral narrative task. This task uses audio recordings of children’s story retells, speech-to-text software and language analysis to record, transcribe, analyse and present oral narrative and listening comprehension data back to class teachers. The task has been designed for class teachers’ use with the support of SLP or literacy specialists in data interpretation. Teachers are upskilled and supported in order to interpret these data and implement teaching practices for students through online professional learning and development modules, within the context of a broader evidence-based approach to early literacy instruction. This article describes the development of this innovative, culturally relevant, online tool for monitoring children’s oral narrative ability and listening comprehension in their first year of school. Three phases of development are outlined, showing the progression of the tool from a researcher-administered task during controlled research trials, to wide-scale implementation with thousands of students throughout New Zealand. The current iteration of the tool uses an automatic speech-recognition system with specifically trained transcription models and support from research assistants to check transcription, then code and analyse the oral narrative. This reduces transcription and analysis time to approximately 7 minutes, with a word error rate of around 20%. Future development plans to increase the accuracy of automatic transcription and embed basic language analysis into the tool, with the aim of removing the need for support from research assistants.